Aluminum dust exposure and risk of neurodegenerative diseases in a cohort of male miners in Ontario, Canada - Xiaoke Zeng; Jill Macleod; Colin Berriault; Nathan L DeBono; Victoria H Arrandale; Anne M Harris; Paul A Demers (Nordic Association of Occupational Safety and Health (NOROSH), 2021)
OBJECTIVES: We estimated associations between respirable aluminum exposure through McIntyre Powder (MP), a fine-sized aluminum and aluminum compound powder, and neurological disease in a retrospective cohort of mining workers from Ontario, Canada. Outcomes included Alzheimer's disease, Alzheimer's with other dementias, Parkinson's disease, parkinsonism, and motor neuron disease. METHODS: The cohort was created by linking a database of mining workers' work history to healthcare records. This analysis included 36 826 male miners potentially exposed to MP between 1943 and 1979, followed up for disease diagnosis between 1992 and 2018. Exposure was assessed using two approaches, self-reported and historical records. Neurological diseases were ascertained using physician billing and hospital discharge records. Poisson regression models were used to estimate associations between MP exposure and neurological outcomes using incidence rate ratios (RR) and 95% confidence intervals (95% CI). RESULTS: Exposure to self-reported MP was associated with an elevated incidence rate of Parkinson's disease (RR 1.34, 95% CI 1.14-1.57). The rate of Parkinson's disease appeared to increase with the duration of exposure assessed by historical records. Having ever been exposed to MP was positively associated with an elevated rate of Alzheimer's with other dementias (RR 1.12, 95% CI 1.06-1.19) but not Alzheimer's disease alone. CONCLUSION: This study found that miners who were exposed to MP (respirable aluminum) had elevated rates of Parkinson's disease. The rate of Parkinson's disease appeared to increase with the duration of exposure assessed by historical records.